Eye development and developmental expression of crystallin genes in the long arm octopus, Octopus minor - Ryu, Kyoung-Bin; Jo, Gun-Hee; Gil, Young-Chun; Jeon, Donggu; Choi, Na-Rae; Jung, Seung-Hyun; Jo, Seonmi; An, Hye Suck; Lee, Hae-Youn; Eyun, Seong-il; Cho, Sung-Jin (Frontiers in Marine Science, 2023)
The eye of a cephalopod is a well-known example of convergent evolution and resembles the vertebrate eye. Although cephalopods and vertebrates exhibit similar eye form and function, they differ in visual origin and structure. The common long-arm octopus (Octopus minor) is a good model system in evolutionary and developmental studies due to its highly centralized nervous system, shorter life cycle, and specific camera-type eyes that contribute to convergence with vertebrate eye. Lens-containing eyes represent a significant improvement of simple eye and have evolved by convergent mechanisms, a variety of lenses and corneas containing diverse crystallin. The diversity and taxon-specificity of lens crystallin is indicative of convergent evolution of crystallin roles. Previous studies have focused on morphological, ontogenetic and phylogenetic analysis of crystallin to understand the evolution of lens-containing eyes. However, little is known about the functional analysis of taxon-specific crystallin genes at the molecular level in the eye of O. minor. Using an embryonic staging system of Octopus minor as a model system, we investigated fifteen genomes and the structure of eye by immunohistochemistry, phalloidin staining and the three-dimensional structures. We also obtained the crystallin-related genes (i.e., α-, S-, and Ω-crystallin) from the transcriptome data of O. minor. Subsequent molecular phylogenetic analysis based on these genes revealed a distinct divergence pattern among the three gene classes and further suggested the evidence supporting the taxon-specific convergent evolutionary trend. We analyzed the expression pattern of crystallin genes via in situ hybridization during developmental stages. All crystallin genes are commonly expressed in the lentigenic cells of ciliary body. The α-crystallin found in cephalopods was also expressed at the peripheral region of the lens including ciliary body, suggesting a possible role in lens formation in cephalopods. This study will provide information on the eye development of O. minor and support the typical models of convergent evolution by demonstrating independent recruitment of different types of proteins to fulfill their unique visual role.